DENNIS DYERS PROPOSAL FOR STATE BCIAS - FERNICOLA SUHR K (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Memo to Susan Stuntz from Karen Fernicola Suhr regarding Dennis Dyer's proposal for state Business Councils on Indoor Air (BCIA). Cites membership, activities, control, scope, and cost as major concerns with the proposal. Recommends Dyer's proposal be modified to be confined to one state, have a "more logical member base," place more emphasis on gaining credibility with policy makers, and remove references to labor.